The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1002/qua.25435
|View full text |Cite
|
Sign up to set email alerts
|

Uncatalyzed peptide bond formation between two double amino acid molecules in the gas phase

Abstract: The gas phase mechanism for peptide bond formation between two double amino acid (DAA) molecules ((NH2)2C(COOH)2) is investigated in the absence of any catalysts. Two different paths, concerted and stepwise, each leading to both cis and trans DAA‐DAA dipeptide products (four mechanisms total) are examined on the basis of theoretical calculations carried out at the CCSD(T)/aug‐cc‐pVDZ//MP2/aug‐cc‐pVDZ level. The investigation indicates that the concerted mechanism leading to the trans configuration of the pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…A natural environment for such abiotic synthesis to occur is within amino acid clusters. Various amino acids (although not all) are known to form stable noncovalent complexes both in solution and in the gas phase. Theory suggests that the orientation of the OH···H mode of hydrogen bonding between neighboring amino acid molecules in clusters is suitable for bond formation, suggesting that peptides can be formed even in the gas phase . Nevertheless, for bond formation energy must be deposited into the cluster, and consequently the evaporation of molecules from the cluster will compete with peptide bond formation.…”
mentioning
confidence: 99%
“…A natural environment for such abiotic synthesis to occur is within amino acid clusters. Various amino acids (although not all) are known to form stable noncovalent complexes both in solution and in the gas phase. Theory suggests that the orientation of the OH···H mode of hydrogen bonding between neighboring amino acid molecules in clusters is suitable for bond formation, suggesting that peptides can be formed even in the gas phase . Nevertheless, for bond formation energy must be deposited into the cluster, and consequently the evaporation of molecules from the cluster will compete with peptide bond formation.…”
mentioning
confidence: 99%
“…The presence of a water molecule during the formation of DAA-DAA dipeptide has been proven important regardless of the conformation of the final product as the energy barriers predicted for the water-assisted mechanisms are significantly reduced in comparison to the barriers found for the corresponding uncatalyzed reactions [27]. In order to explain the catalytic role of the H 2 O molecule in this process, one may follow the speculation provided in ref.…”
Section: Discussionmentioning
confidence: 98%
“…Its stability with respect to both unimolecular deamination and decarboxylation reactions has already been addressed in order to show that spontaneous detachment of either ammonia or the carbon dioxide molecule in gas and aqueous phases is not operative [24,25]. Moreover, we demonstrated that the DAA system acts similarly to various natural amino acids when the noncatalyzed peptide bond formation process between two DAA molecules or the cyclization involving two DAAs in gas phase are considered [26,27].…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Amino acid clusters (dimer and tetramer clusters of α-alanine) have been studied by theory as precursors for polypeptide formation as the orientation of the OH ⋯ NH mode of hydrogen bonding is found to be suitable for chemical condensation 15 . In the case of two glycine molecules 16 or double amino acids 17 , different mechanisms for peptide bond formation have been mapped out with quantum mechanical electronic structure methods. Furthermore, peptide bond formation has also been suggested to be initiated by glycine protonated at the hydroxyl oxygen 18 .…”
mentioning
confidence: 99%